Development of Teaching Materials for the Concept of Pancasila and Citizenship Education Based on Higher Order Thinking Skills - Herawati, Herawati; Akmaluddin, Akmaluddin; Syarfuni, Syarfuni; Syafii, Mhd.; Sari, Siti Mayang; Norhazaruddin, Nurul Fatehah Binti (Jurnal Pendidikan Humaniora, 2025)
This study aims to develop teaching materials for the concept of Pancasila and Citizenship Education based on Higher Order Thinking Skills to improve the learning outcomes of fifth grade students. This study is a development research with a descriptive quantitative research method through the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the analysis, data was obtained that the average student score before the action with a total percentage of completion scores of 70% with a minimum completion score of 75 was categorized as not having increased with the average percentage of the value obtained. Through the development of HOTS-based PPKN textbooks with an average validity value of 98%, it was declared very feasible to implement. Based on the results of the teacher's response, the score was 90% with a very feasible category, and the student's response was 93% stated as very feasible. After carrying out HOTS-based research activities, student learning outcomes increased from the posttest results, obtaining an average score of 91% with very good criteria with details of 24 students completing.